Dari Gold-Tree, Hase-Hime, Balna, hingga Bawang Putih: Dongeng Sebagai Media dalam Pemahaman Interkultural - Amalia Rachmawati; Tengsoe Tjahjono; Resdianto Permata Raharjo (Universitas 17 Agustus 1945 Surabaya, 2022)
Currently the importance of Intercultural understanding has no doubted. People can not resist the existence of world Englishes or English as international language which require not only the ability to use English language but also to use English language respectfully across culture. To achieve those goals, the intercultural understanding is highly needed. One of the ways that can be done to gain intercultural understanding is through reading fairy tales. The aim of this study is to investigate and analyze the possibility to use fairy tales for fostering young learners’ intercultural understanding. It employed qualitative descriptive method and comparative literature to analyze the data. The data used Celtic, Japanese, Indian, and Indonesian fairy tales that have the same theme then it compared to pointing out the cultural aspects. The finding revealed that despite the similarities in the plots, the fairy tales from various countries depicted the differences in cultural aspect. Thus, can be inferred that the fairy tales can be an option as a vehicle to build young learners’ intercultural understanding